WHATSAPP AS A MOBILE LEARNING ENVIRONMENT FOR ENGLISH AS A FOREIGN LANGUAGE (EFL) STUDENTS - Nurmayasari, Dewi (2017)
This study investigates the use of WhatsApp to support face-to-face classroom activities. WhatsApp as a mobile learning environment is expected to be a medium that provides the opportunity for the students to learn anywhere and at any time (Crescente &Lee, 2011). More specifically, this study examines (1) To what extent, WhatsApp as a mobile learning environment can support EFL students' learning outside classroom, (2) what the students' responses to the use of WhatsApp are. This study employed a qualitative research design. Thirteen students at one of English courses in Bandung were participants in this study. This study used three techniques in data collection; they were WhatsApp group observation, questionnaires, and interview. Data from observation were analyzed quantitatively and qualitatively to investigate the activities in WhatsApp group. Then data of questionnaire were analyzed by using Likert Scales. Data from interviews were transcribed, analyzed and categorized to answer the research questions that were used as a part of data triangulation. The study reveals that WhatsApp as a mobile learning environment can support EFL students learning outside classroom, where they could practice and communicate in English using seven WhatsApp features (group chats, send photos, send voice note and audio; send documents, make text bold, italics and strikethrough; quote messages for clear replies, see when your messages are read). Students' responses to the use of WhatsApp as a mobile learning environment is positive. It means that WhatsApp supported them in learning process; furthermore, it enhanced their confidence and motivation to communicate in English.